Plano de negócio para uma empresa de distribuição de equipamentos de led na cidade de Porto Alegre/RS - Venturini, Neimar Druzian (Universidade do Vale do Rio dos Sinos, 2014)
The business plan is a valuable planning tool, an important tool that helps future entrepreneurs to organize your ideas and develop your action plan and map your route more objectively and with calculated risks. It is through it that we can analyze the feasibility or not of opening a new business. This study addresses the analysis of the feasibility of starting a business of importing and distributing equipment for LED lighting with own brand in Porto Alegre / RS. LED lamps offer great potential application due to its high efficiency coupled with good performance lighting and positive impact in relation to the environment, establishing itself as a good alternative that is occupying more and more space in the world for the replacement of incandescent and fluorescent lamps. The primary sources of energy are limited, a fact that highlights the need for investment in energy efficiency projects. In this sense, similar to what occurred in the early 2000s, when large quantities of compact fluorescents lamps entered the Brazilian market due to the blackout, one observes a similar situation today with LED products. Seeing this trend, and based on the main concepts of strategic planning, this study seeks to identify the advantages in the creation of a distribution company for lighting equipment through LED.
Keywords: Empreendedor; Plano de negócio; Pesquisa de mercado; Iluminação; LED; Entrepreneur; Business plan; Market research; Lighting